1999
DOI: 10.1017/s0043174500092183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors on germination and emergence ofAmaranthus retroflexus

Abstract: Detailed knowledge about the environmental conditions required for weed seed germination and establishment in soil is an important prerequisite for the development of integrated and biological weed control strategies. Germination and establishmentof Amaranthus retroflexuswere studied at different temperatures, planting depths, soil types, nitrogen supply, and water potentials. The minimum temperature for seed germination was > 5 C; maximum germination occurred between 35 and 40 C. At temperatures between 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 17 publications
10
77
1
2
Order By: Relevance
“…They realized that although light can be a requirement in some seeds, this requirement can often be overcome by warmer germination temperatures and can vary with seasonal seed dormancy fluctuations. Results of this study were in agreement with those obtained by Siriwardana and Zimdahl (1984), Martinez et al (1992), and Ghorbani et al (1999). By sensing the most favorable environmental signals, natural factors (light, temperature, rainfall, etc.…”
Section: Resultssupporting
confidence: 90%
“…They realized that although light can be a requirement in some seeds, this requirement can often be overcome by warmer germination temperatures and can vary with seasonal seed dormancy fluctuations. Results of this study were in agreement with those obtained by Siriwardana and Zimdahl (1984), Martinez et al (1992), and Ghorbani et al (1999). By sensing the most favorable environmental signals, natural factors (light, temperature, rainfall, etc.…”
Section: Resultssupporting
confidence: 90%
“…Some results of germination ecology and response to environmental factors were reported by weed scientists [2632]. Amaranthus is also the genus with several naturalized weeds including the highly invasive A .…”
Section: Introductionmentioning
confidence: 99%
“…Buhler et al (1994) have noticed greater and more diverse populations of perennial weeds under RT systems in corn-soybean rotations. Buhler (1995) found that the densities of large-seeded dicot species often decreased under RT in corn-soybean rotation as minimizing soil disturbance affected the composition of weed communities (Zanin et al, 1997), e.g., small-seeded weeds, such as pigweeds, emerged only from shallow burial depths (0.5-2.5 cm) (Buhler et al, 1996;Ghorbani et al, 1999;Oryokot et al, 1997). Torresen et al (1999) found that due to survival of more weeds to the next growing season more seeds were produced as compared to autumn ploughing at Norway.…”
Section: Reduced/minimum Disturbance Systemsmentioning
confidence: 99%